Esterification of malic acid on various catalysts - N. S. Kuzmina; S. V. Portnova; E. L. Krasnykh (Тонкие химические технологии, 2020)
Objectives. The study aims to identify the optimal choice of an effective catalyst for the esterification of malic acid to produce esters of high purity. Methods. To determine the qualitative and quantitative composition of reaction masses, the following analysis methods were used: mass-spectroscopy (using FinniganTrace DSQ device with NIST 2002, Xcalibur 1.31 Sp 5 database) and gas–liquid chromatography (using the Kristall 2000M software and hardware complex). Results. Esters of malic acid and butyl alcohol of normal structure were synthesized using the following catalysts: sulfuric, orthophosphoric, p-toluenesulfonic acid, Amberlyst 36 Dry, Amberlyst 36 Wet, KU-2-FPP, and KIF-T. The obtained products were analyzed by gas–liquid chromatography. The structure of the products was confirmed by mass spectrometry. Schemes for the formation of byproducts are proposed. The yields and purity of the malic acid butyl esters obtained using different catalysts were evaluated. The results show that the heterogeneous catalyst Amberlyst 36 Dry is optimal for obtaining a pure malic acid ester with a maximum yield. Conclusions. The results show that during the esterification of malic acid with butyl alcohol of normal structure, byproducts, such as esters of fumaric and maleic acids, are formed using different catalysts. An accumulation of byproducts occurs as a result of reactions of dehydration of malic acid or its ester. The results also show that the number of byproducts is almost independent of the catalyst, with the exception of sulfuric acid. The Amberlyst 36 Dry catalyst provides an optimal ratio between conversion and selectivity for malic acid dibutyl ester production.